"Phantom of the Opera" or "Sex and the City"? Historical Amenities as Sources of Exogenous Variation - Thomas K. Bauer; Philipp Breidenbach; Christoph M. Schmidt (Institute for the Study of Labor (IZA), 2014)
Using the location of baroque opera houses as a natural experiment, Falck et al. (2011) claim to document a positive causal effect of the supply of cultural goods on today's regional distribution of talents. This paper raises serious doubts on the validity of the identification strategy underlying these estimates, though. While we are able to replicate the original results, we proceed to show that the same empirical strategy also assigns positive causal effects to the location of historical brothels and breweries. These estimated effects are similar in size and significance to those of historical opera houses. We document that all these estimates reflect the importance of institutions for long-run economic growth, and that the effect of historical amenities on the contemporary local share of high skilled workers disappears upon controlling for regions' historical importance.
Keywords: R11; H42; J24; 330; human capital; historical amenities; regional competiveness